2015
DOI: 10.14735/amko2015177
|View full text |Cite
|
Sign up to set email alerts
|

Anxio- depressive Syndrome – Biopsychosocial Model of Supportive Care

Abstract: 1 I. onkologická klinika LF UK a Onkologický ústav sv. Alžbety, Bratislava, Slovenská republika 2 Katedra farmakológie, Farmakologická fakulta, UK v Bratislave, Slovenská republika 3 Katedra verejného zdravotníctva, Vysoká škola zdravotníctva a sociálnej práce Sv. Alžbety, Bratislava, Slovenská republika SúhrnVýchodiská: Akútny stres vyvolaný dia gnózou rakoviny a posttraumatický stresový syndróm, ktorým trpia prežívajúci pa cienti s nádorovou chorobou, spôsobuje pokles kvality života pa cientov najmä v dôsled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Possible explanations for the associations have been suggested, including a direct effect on neuro‐endocrinological and/or immunologic systems or an indirect effect via changes in behavior. Potential physiological pathways have been shown to contribute to the cross‐talk between AE and the development, progression, and control of cancer, including the sympathetic nervous system, hypothalamic pituitary adrenal axis, stress hormones, cellular immunity, inflammation, angiogenesis, invasion, anoikis, and changes in gene expression, as well as telomere length and telomerase activity, which could interact with the tumor microenvironment to promote factors favoring tumor growth . The most likely biobehavioral mechanisms underlying the relationship between AE and survival include poor adherence to anticancer treatment, fewer social networks, and disruptions of circadian rhythms such as sleep/activity .…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the associations have been suggested, including a direct effect on neuro‐endocrinological and/or immunologic systems or an indirect effect via changes in behavior. Potential physiological pathways have been shown to contribute to the cross‐talk between AE and the development, progression, and control of cancer, including the sympathetic nervous system, hypothalamic pituitary adrenal axis, stress hormones, cellular immunity, inflammation, angiogenesis, invasion, anoikis, and changes in gene expression, as well as telomere length and telomerase activity, which could interact with the tumor microenvironment to promote factors favoring tumor growth . The most likely biobehavioral mechanisms underlying the relationship between AE and survival include poor adherence to anticancer treatment, fewer social networks, and disruptions of circadian rhythms such as sleep/activity .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a metanalysis with cancer and cancer-depressed patients [58] concluded that management of stress-linked-emotions (which include serotoninergic alterations) is a crucial element to (i) prevent comorbidities related to disruption of endocrine and autonomic (sympathetic) nervous system homeostasis; and (ii) improve survival time in these patients. Hence, stabilizing 5-HT levels may be a strategy to prevent autonomic disorders as comorbidities in diseases with associated high emotional stress.…”
Section: Clinical Relevance and Therapeutic Potentialmentioning
confidence: 99%